2010
DOI: 10.1007/s12011-010-8911-y
|View full text |Cite
|
Sign up to set email alerts
|

Chemometric Studies of Multielemental Composition of Few Seagrasses from Gulf of Mannar, India

Abstract: This paper discusses the determination of minerals content (cadmium, cobalt, chromium, copper, nickel, lead, manganese, magnesium, iron, zinc, sodium, potassium and calcium) of six seagrass samples, Enhalus acoroides, Thalassia hemprichii, Halodule pinifolia, Syringodium isoetifolium, Cymodocea serrulata and Cymodocea rotundata using inductively coupled plasma optical emission spectrophotometry and flame photometer. Principal component analysis (PCA) and hierarchical cluster analysis revealed different mineral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 54 publications
(46 reference statements)
1
1
0
Order By: Relevance
“…Cu and Zn accumulation in the seagrass are less than maximum permissible limits prescribed for seafood for human consumption (10 mg/kg, 50 mg/kg respectively) in India [12]. Similar to the studies of Ragupathi Raja Kannan et al, [13] the levels of essential elements like Fe, Mn, Cu and Zn were higher than the level of non-essential elements like Pb Since, unlike other types of contaminants heavy metals cannot be eliminated as they occur naturally all over the world. Most of the metals play a vital role in the biological metabolism such as Fe (hemoglobin, SOD, CAT), Cu (respiratory pigments), Zn (SOD), Co (Vitamin B12), Mo and Mn (enzyme cofactor) [14].…”
Section: Resultssupporting
confidence: 69%
“…Cu and Zn accumulation in the seagrass are less than maximum permissible limits prescribed for seafood for human consumption (10 mg/kg, 50 mg/kg respectively) in India [12]. Similar to the studies of Ragupathi Raja Kannan et al, [13] the levels of essential elements like Fe, Mn, Cu and Zn were higher than the level of non-essential elements like Pb Since, unlike other types of contaminants heavy metals cannot be eliminated as they occur naturally all over the world. Most of the metals play a vital role in the biological metabolism such as Fe (hemoglobin, SOD, CAT), Cu (respiratory pigments), Zn (SOD), Co (Vitamin B12), Mo and Mn (enzyme cofactor) [14].…”
Section: Resultssupporting
confidence: 69%
“…According to WHO, the concentration of trace elements must be controlled in medicinal plants in order to meet the quality assurance. Thus, the investigation of toxic and trace elements in food and medicinal plants has been targeted (Gomez et al, 2007;Kara, 2009;Maiga, Diallo, Bye, & Paulsen, 2005;Nookabkaew, Rangkadilok & Satayavivad, 2006;Ragupathi Raja Kannan, Arumugam, & Anantharaman, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…Seagrass tissues; This study References Min (mg kg -1 ) Max (mg kg -1 ) Min (mg kg -1 ) Max (mg kg Jagtap, 1983;Mathevan, 1990;Kannan et al, 1992;Nobi et al, 2010;Kannan et al, 2011;Govindaswamy et al, 2011;Gopinath et al, 2011;Sudharsan et al, 2012;Thangaradjou et al, 2013;Immaculate et al, 2018;Arisekar et T. hemprichii (N) T. hemprichii (B) Jagtap, 1983;Mathevan, 1990;Kannan et al, 1992;Nobi et al, 2010;Govindaswamy et al, 2011;Kannan et al, 2011;Sudharsan et al, 2012;Thangaradjou et al, 2013;Arisekar et al, 2021 Mathevan, 1990;Kannan et al, 1992;Nobi et al, 2010;Kannan et al, 2011;Gopinath et al, 2011;Sudharsan et al, 2012;Govindaswamy et al, 2012;Thangaradjou et al, 2013;Immaculate et al, 2018;Gopi et al, 2020;Arisekar et al,…”
Section: Seagrassmentioning
confidence: 89%
“…A recent review on trace metal bioindicator potential of India's marine macrophytes (e.g., seagrasses and saltmarshes), have suggested that seagrass are better bioindicators of trace metal accumulations than saltmarsh plants that inhabit similar intertidal zones (Mishra and Farooq, 2022;Nazneen et al, 2022). Small seagrass species like Halophila ovalis, Halophila beccarii and Halodule uninervis were found to be better bioindicators of various trace metals due to their higher growth rates and gorilla way of meadow expansion (Arisekar et al, 2021;Govindasamy & Azariah, 1999;Jagtap, 1983;Nazneen et al, 2022;Ragupathi Raja Kannan et al, 2011;Sachithanandam et al, 2020a) . However, bioindicator potential of large seagrass species like Enhalus acoroides and Syringodium isoetifolium may be higher than the small seagrass species, but data on trace metal accumulations in these big seagrasses that are present below 5m depth are very low in India (Arisekar et al, 2021;Nobi et al, 2010;Thangaradjou et al, 2010) .…”
Section: Introductionmentioning
confidence: 99%